Genome-wide identification, characterization, and expression analysis of the monovalent cation-proton antiporter superfamily in maize, and functional analysis of its role in salt tolerance - Kong, Mengsi; Luo, Meijie; Li, Jingna; Feng, Zhen; Zhang, Yunxia; Song, Wei; Zhang, Ruyang; Wang, Ronghuan; Wang, Yuandong; Zhao, Jiuran; Tao, Yongsheng; Zhao, Yanxin (Genomics (San Diego, Calif.), 2021)
Na+, K+ and pH homeostasis are important for plant life and they are controlled by the monovalent cation proton antiporter (CPA) superfamily. The roles of ZmCPAs in salt tolerance are not fully elucidated. In this study, we identified 35 ZmCPAs comprising 13 Na+/H+ exchangers (ZmNHXs), 16 cation/H+ exchanger (ZmCHXs), and 6 K+ efflux antiporters (ZmKEAs). All ZmCPAs have transmembrane domains and most of them were localized to plasma membrane or tonoplast. ZmCHXs were specifically highly expressed in anthers, while ZmNHXs and ZmKEAs showed high expression in various tissues. ZmNHX5 and ZmKEA2 were up-regulated in maize seedlings under both NaCl and KCl stresses. Yeast complementation experiments revealed the roles of ZmNHX5, ZmKEA2 in NaCl tolerance. Analysis of the maize mutants further validated the salt tolerance functions of ZmNHX5 and ZmKEA2. Our study highlights comprehensive information of ZmCPAs and provides new gene targets for salt tolerance maize breeding. •We are the first to genome-widely identify monovalent cation-proton antiporter (CPA) superfamily in maize.•The 35 CPA genes include 13 Na+/H+ exchangers (ZmNHXs), 16 cation/H+ exchanger (ZmCHXs) and 6 K+ efflux antiporters (ZmKEAs).•Yeast complementation experiments and maize mutant analysis validated the salt tolerance functions of ZmNHX5 and ZmKEA2.